Epidemiology and risk factors of chronic kidney disease in rural areas (Badin) of Sind, Pakistan - Shahnawaz Kareem; Asifa Jamali; Salam Ali; Muhammad Yousif Arbab; Beena Salman; Salman Imtiaz (Journal of the Pakistan Medical Association, 2023)
Objectives: To evaluate the epidemiology of chronic kidney disease in a rural setting. Method: The retrospective study was conducted at Indus Hospital, Badin, Sindh, Pakistan, and comprised data of patients of either gender regardless of age who visited the nephrology clinic between July 2019 and July 2020. Data was retrieved from the institutional health management information system. Data was analysed using SPSS 21. Results: Of the 348 patients, 184(52.9%) were males and 164(47.1%) were females. The overall mean age was 40.4±19 years. Obstructive nephropathy was the most frequent cause of chronic kidney disease 108(31%), followed by chronic kidney disease of unknown aetiology 79(22.7%). The most prevalent comorbid was hypertension in 106(30.5%) patients, while 56(16.1%) were diabetic. The stone disease was found in 90(24.6%) patients. Age was strongly associated with chronic kidney disease (p<0.001). Among those with chronic kidney disease of unknown aetiology, 35(44.3%) patients were aged 31-50 years 35. The expected glomerular filtration rate in such patients was significantly associated with the cause of chronic kidney disease (p<0.001). Conclusion: Unknown aetiology and kidney stones were the leading causes of chronic kidney disease among the rural population studied. Key Words: Chronic kidney disease, Agricultural communities, Developing country, Kidney stone, Unknown aetiology.